Process evaluation of student health promotion programmes in rural Sabah - Naing Oo Tha; Mohd Yusof Ibrahim; Patricia Sator; Rajesh Kumar Muniandy; D Kamarudin D Mudin; Mohammad Saffree Jeffree (2019)
The Faculty of Medicine & health sciences, UMS has implemented a co-curricular programme which is aimed to be improving rural health and reducing inequalities of health in Sabah. Groups of medical students are formed and distributed in various areas of rural remote areas in Sabah. Based on the observation and interview findings, each student group conducted health promotion activities with the limited resources. Various health problems were explored in different areas and different ethnic groups of Sabah and students conducted their health promotion activities .There are some questions “Are they effective, how it works in implementation?” Poor implementation can lead to errors in outcome of the programmes. In this paper we focus on process evaluation for measuring the degree to which Health promotion programmes were implemented as designed by using determinant framework (active implementation framework) and process evaluation tools in yearly health promotion programmes from 2009-2018. Methods: The study measures the implementation of programmes with active implementation framework (Exploration, Installation, Initial implementation, Full implementation) and process evaluation tools such as validation of implementation integrity using specification of intervention areas, making guidelines and manual for intervention protocol, competency of students and supervisors and fidelity monitoring. We used 7 components of process evaluation particularly in context( Environmental influences), reach (Target participation), dose delivered (Lectures), dose received (learned by students with assessment methods), fidelity (Adherence to intervention delivery protocol), implementation (rating of execution and receipt of intervention) and recruitment (participant engagement). Results: It was found that fidelity, implementation strategies and some lessons learned after outreach programmes are importantly influence in implementing the programmes. Conclusion: The study shows process evaluation strategies is ideal tool for conducting the rural outreach health promotion programme to reduce the errors and obstacles in implementing the programmes to maintain the better quality of the projects.